A modified Terrono classification for Type 1 thumb deformity in rheumatoid arthritis: a cross-sectional analysis. (February 2020) - Toyama, Shogo; Oda, Ryo; Asada, Maki; Nakamura, Satoru; Ohara, Masato; Tokunaga, Daisaku; Mikami, Yasuo
The most common thumb deformity in rheumatoid arthritis is Nalebuff Type 1 deformity (boutonniere deformity). Type 1 deformity severely impairs hand function, and this impairment is evaluated by the Terrono classification. In some cases, the Terrono classification incorrectly categorizes advanced thumb deformity into earlier stages. We modified the Terrono classification by assessing the active range of motion of the interphalangeal joint prior to assessing the passive range of movement of the metacarpophalangeal joint. An active range of movement of the interphalangeal joint was strongly correlated with hand function. In 55 hands that we treated between 2004 and 2015, we compared the modified classification with the original Terrono classification. Our modified classification could detect advanced deformity earlier, and was more strongly correlated with hand function. Additionally, correlation analysis showed that advanced Type 1 deformity should be treated first, even in cases with severe ulnar drift. Our results suggest that the modified classification may benefit the treatment of Type 1 deformity, including joint-preserving surgery. Level of evidence: III